Sustainable Horizons: A Review on Sustainable Processing, Quality Enhancement, and Safety Assurance in Aquatic Food Products - Yesilsu, Ahmet Faruk; Alak, Gonca; Alp Erbay, Esen; Sagdic, Osman; Ozogul, Fatih; Demirkesen, Ilkem; Rathod, Nikheel B.; Bozkurt, Fatih; Alasalvar, Cesarettin; Benjakul, Soottawat; Jambrak, Anet Rezek; Aydin, Ilhan (TAYLOR & FRANCIS INC, 2025)
Examining recent innovations in aquatic food products shows significant progress in sustainable processing, product quality, and safety. The introduction of nano-encapsulation and innovative packaging methods has undeniably propelled the industry forward. These developments have proven effective in preventing microbial growth and moderating changes in product quality alterations. In addition, technologies such as colorimetric sensors and oxygen scavengers have brought fresh perspectives to real-time food quality monitoring and control, further solidifying their contribution to the industry's growth. Despite these advances, challenges persist, particularly in the areas of food safety and environmental conservation. The paper emphasizes the need for robust and responsive risk assessment measures and effective mitigation strategies. These can prevent potential biological, chemical, and environmental hazards, thereby improving food safety and safeguarding our precious ecosystems. The review also highlights the importance of the regulations that strike a balance between meeting consumer preferences, enforcing environmental conservation, and prioritizing sustainability to drive the industry toward a prosperous future. The insights from this review serve as a crucial roadmap for various stakeholders in the industry, providing direction for decision-making, and fostering advancements in sustainable processing, quality enhancement, and safety assurance within the aquatic food industry.
Keywords: Sustainable processing; quality enhancement; risk assessment; mitigation strategies; regulatory framework; environmental conservation; aquatic food products; SHRIMP LITOPENAEUS-VANNAMEI; ESSENTIAL OILS; ARGININE KINASE; SEAFOOD ALLERGY; FATTY-ACIDS; FISH; TROPOMYOSIN; CHALLENGES; ALLERGENICITY; INACTIVATION; Food Science & Technology; Nutrition & Dietetics